2022
DOI: 10.1002/pmrj.12797
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of anthropometric measurements and percent body fat mass to cardiovascular disease risk factors in adults with cerebral palsy

Abstract: Introduction: Adults with cerebral palsy (CP) face high morbidity from cardiovascular disease (CVD). Of concern, classic screening parameters are inconsistent in identifying CVD risk in this population. Dual-energy x-ray absorptiometry (DEXA), which provides direct measurements of fat mass (FM), may be an alternative screening method. Objective: To evaluate whether FM measurement with DEXA is feasible in screening adults with CP and compare FM and anthropometric measures to CVD risk factors. Design: Cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…In this context, many recent studies have introduced WHtR as an alternative to WC and a better predictor of cardiovascular risk factors (6-8). But studies conducted in different countries have shown different results for these four anthropometric indicators (9,10). It has been proven that the predictive power of anthropometric indices in the risk of CVD depends on the population and varies between different ethnic groups.…”
mentioning
confidence: 99%
“…In this context, many recent studies have introduced WHtR as an alternative to WC and a better predictor of cardiovascular risk factors (6-8). But studies conducted in different countries have shown different results for these four anthropometric indicators (9,10). It has been proven that the predictive power of anthropometric indices in the risk of CVD depends on the population and varies between different ethnic groups.…”
mentioning
confidence: 99%
“…Commonly used clinical methods to screen for and monitor risk of disease have limited value in their current form (e.g. ranges of body mass index for obesity status) for adults with CP 9 because of individuals' different anatomy and physiology (for a review, see Whitney et al 10 ). Classification scales to characterize CP, namely the Gross Motor Function Classification System (GMFCS) 11 and the Manual Ability Classification System (MACS), 12 may broadly differentiate risk of disease outcomes 2,3 .…”
mentioning
confidence: 99%